Characterization and kinetic studies of fat, oil and grease deposition in sewer pipelines - Husain, Iman A.F (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Fat, Oil and Grease (FOG) may cause blockages of the sewer system and are a serious environmental problem. FOG is usually produced at food service establishments (FSE) or any other food preparation facility. In Malaysia, the eating habits of people are changing, people are eating outside home more often and thus the number of food outlets is increasing, which results in more blockages due to FOG deposition. FOG continuous build-up decreases the capacity of the sewer system as it solidifies and deposits on the interior walls of the sewer, causing blockage in pipes and hence restricting the wastewater flow. Over the time, sewers blocked by FOG will fail and overflow out of the manholes, which eventually could make its way to state water sources. This research aims to study the deposition of FOG in sewer systems, its mechanism, rates and causes. The methodology for this research consists of characterization of the physical and chemical constituents of the FOG deposits; a study of the effects of oil, salt, mono sodium glutamate (MSG), and detergent to form FOG particles; a kinetics study of palm oil saponification and FOG deposition; and modeling and simulation of the FOG deposition in sewer pipes. A pilot scale model of a gravity sewer was designed and setup in the lab. Synthetic wastewater was used for simulating actual domestic sewage. Continuous monitoring of the FOG deposition on the pipe wall was done for 20 days. For the computational modeling, multiphase Eularian model with discrete element method (DEM) in ANSYS FLUENT 14.0 was employed to simulate the wastewater-FOG particles flow and deposition in a sewer pipe. The model uses the Eularian method for the wastewater continuous phase while the Lagrangian method is used to solve the motion equations for the FOG particles. The simulations were carried out using a transient solver due to the unsteady state nature of the turbulent flows. The main salts found in the wastewater samples were Sodium (27.56 mg/l) and calcium (25.42 mg/l). Characterization of the deposit samples showed that the FOG deposits are made of metallic soaps that formed during cooking, and deposit in grease traps and/or along the sewer pipes by the saponification reaction of oil and free fatty acids with salts such as sodium (1.71 mg/l), calcium (1.96 mg/l) and potassium (0.77 mg/l). The laboratory scale experiments indicated that FOG particles form at 26±2 °C within few days. Moreover, the factors contributing the most to the formation of FOG particles were oil and salt concentrations. Sodium and calcium were the main salts contributing to the saponification reaction and resulted with 402.5 and 258.335 mg/l FOG as TSS. An oil concentration of 700 mg/L and sodium concentration of 50 mg/l lead to the formation of 433.3 mg/L TSS FOG. Moreover, MSG resulted with the formation of larger volumes of FOG particles (600 mg/l), which indicates that MSG is an important sodium source contributing to deposition and pipe blockages. The pilot scale operation resulted in 5 cm deposition on the pipe wall within 20 days. The kinetics showed that the FOG saponification is an autocatalytic first order reaction exhibiting a sigmoidal kinetic curve. The reaction was at its highest rate between 30 minutes to 240 minutes. Sodium concentration is the limiting factor of the saponification reaction. The CFD Eularian-DEM multiphase model has shown good potential for simulating the wastewater flow and demonstrates the applicability of CFD to simulate and track the transport and deposition of FOG particles onto the sewer pipe walls.